ANALISIS IDENTITAS BUDAYA POPULER JEPANG TERHADAP KOMUNITAS ANIME PALEMBANG - Arsi Pri nando; Darwadi MS; Septiana Wulandari (Jurnal Komunikasi dan Budaya, 2022)
ABSTRACTHumans in daily lives can’t be separated from the name of culture. For example, popular culture is a culture that produces a value in the form of economics or politics. Like a Japanese popular culture in Indonesia is now growing rapidly with many media that can access it, such as Anime and Manga, not only that Japan has also expanded its popular culture in the culinary and fashion fields.There are many enthusiasts of Japanese popular culture in Indonesia, for example the Palembang Anime Community. This study uses the Social Identity theory because this studies aims to see how popular culture develops within a group. This study uses a qualitative method in which researchers can obtain information and learn everything related to the Palembang anime community then presented and analyzed using theory. From the results of the analysis that the researchers conducted, it was found that the Palembang anime community is a community that uses Japanese culture in its identity like a copy language, style, as well change the nick name to be Japan Name.Keyword : Popular Culture, Palembang Anime Community, Anime Culure